Electronic gaming addiction among adolescents: A predictive structural analysis of demographic and behavioral factors - Yahya, Khatatbeh; Bani Yassin, Omar Saleh; Waed F, Mistarihi (Research Journal in Advanced Humanities, 2025)
Background: The growing engagement of adolescents with electronic games has raised concerns about gaming addiction. Understanding how behavioral and demographic factors contribute to this phenomenon is crucial, especially concerning game type, play mode, and daily usage.Objectives: This study aimed to investigate the impact of game type, play mode (online/offline), gameplay hours, birth order, gender, and parental education level on electronic gaming addiction among adolescents.Methods: A non-experimental quantitative design using a descriptive-analytical approach was adopted. The sample consisted of 312 adolescents selected via stratified random sampling. The Game Addiction Scale for Adolescents was utilized, and data were analyzed using Multivariate Analysis of Variance (MANOVA) and Structural Equation Modeling (SEM).Results: Gameplay hours and game type—particularly combat games—emerged as the strongest predictors of gaming addiction. Play mode had no significant effect. Males exhibited higher levels of addiction than females. Higher maternal education was associated with lower addiction scores. Academic achievement did not mediate the relationship between parental education and addiction.Conclusion: The findings underscore the need for preventive psychological and educational programs targeting screen time and gaming content. Future studies should explore emotional, social, and neurocognitive variables to enhance the understanding of digital addiction mechanisms.